KOMPLEKSITAS SIMBOL DAN REPRESENTASI MAKNA DALAM TRADISI RAJABAN MASYARAKAT KEBUMEN - Siti Fathonah (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2018)
This study tries to describe the behavioral-practice and to find out the meaning behind the symbols represented by the Kebumen society through the Rajaban tradition. Kebumen, which is known as the meeting point between the traditions of Islamic Mataram of Yogyakarta which is identically close to the culture of priyayi, and the Banyumasan tradition which is identically known as peripheral community, become its unique consideration of the selected locations of the study. Through an ethnographic approach, based on the theoretical basis of symbolic functionalism as its analysis perspective, the results of the study showed that there is a layer of meaning represented by various symbols used by the Kebumen community during the Rajaban tradition practice. First, the social meaning is the orientation of the community in presenting â€œberkatâ€. The â€œberkatâ€â€™s form and model representing the socio-economic status of its provider. Second, "janengan" as an important part in the process of reciting the Prophet's prayer, is believed to be one form of respect for the da'wah that has been carried out by the Wali in spreading Islam in Java.